43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-1105
|View full text |Cite
|
Sign up to set email alerts
|

Ship Airwake Sensitivities to Modeling Parameters

Abstract: Accurate models for the prediction of ship airwake flowfields are critical to the development of realistic flight simulation tools for aircraft carrier launch and recovery operations. The accurate computation of the ship airwake can be very challenging due to the complexity of the ship geometry, the size of and difficulty in generating a suitable computational mesh, and the large range of length and time scales present in the unsteady flowfield. The present paper investigates the sensitivity of the airwake sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…19,23,27 (iii) Since the GAC is intended as a simplified, geometric benchmark model for aircraft carrier studies, intricate details like sensors and minor equipment mounted on the island or the flight deck have been omitted and only the major structures are retained. Studies by Shipman et al 32 support this argument, that such small structures would not create effects of a magnitude that is of interest to a generalized study like the present work. Thus, the GAC has resulted in a simplified geometry that is easy to fabricate and duplicate experimentally or simulate numerically for CFD studies, meshing requirements around the canonical forms used in the GAC are far more forgiving than complex three-dimensional geometries.…”
Section: Proposal Of Generic Aircraft Carriersupporting
confidence: 67%
“…19,23,27 (iii) Since the GAC is intended as a simplified, geometric benchmark model for aircraft carrier studies, intricate details like sensors and minor equipment mounted on the island or the flight deck have been omitted and only the major structures are retained. Studies by Shipman et al 32 support this argument, that such small structures would not create effects of a magnitude that is of interest to a generalized study like the present work. Thus, the GAC has resulted in a simplified geometry that is easy to fabricate and duplicate experimentally or simulate numerically for CFD studies, meshing requirements around the canonical forms used in the GAC are far more forgiving than complex three-dimensional geometries.…”
Section: Proposal Of Generic Aircraft Carriersupporting
confidence: 67%
“…However, the size of the wake behind the yardarm poles is again over-predicted even for this case. In addition to applying the IBC approach, a parallel effort was executed that employed standard surface gridding techniques to grid the actual antenna structure (Shipman et al, 2005). The CFD code CRUNCH was used for this portion of the study.…”
Section: Velocity Deficitmentioning
confidence: 99%
“…Results by Shipman et al (46) investigated the effects of geometrical representation of the ships on the quality of the airwake prediction, concluding that reasonable simplifications can be made to the ships superstructure without greatly affecting the majority of the airwake. Additionally, they note that including boundary layer resolving grid components only marginally improves the simulation quality.…”
Section: Grid Generationmentioning
confidence: 99%
“…Note that in generating the grids no attempt was made to model the boundary layer attached to the ship. This simplification of the meshing requirements makes the prediction of flow separation from gradually curved surfaces less accurate, however previous studies by Shipman et al (46) investigated in depth the effects of resolving the boundary layer and concluded it has minimal influence on the quality of the wake prediction in terms of mean and fluctuating velocities. It is not clear in the paper of Shipman et al whether the resolved boundary layer study had the same number of points, and same computational time as the unresolved case.…”
Section: Grid Generationmentioning
confidence: 99%
See 1 more Smart Citation